Memory and credibility perceptions of alcohol and other drug intoxicated witnesses and victims of crime. Issue 8 (14th September 2022) - Monds, Lauren Ann; Cullen, Hayley Joanne; Kloft, Lilian; van Golde, Celine; Harrison, Anthony William; Flowe, Heather
ABSTRACT: Research into juror perceptions regarding the impact of intoxication on eyewitness memory and credibility is scarce for substances other than alcohol. However, jurors are frequently told to draw on their personal beliefs and experience with intoxicating substances to infer their impact on the case. It is therefore important to investigate laypeople's perceptions regarding witness and victim intoxication across a range of substances, and whether these perceptions are associated with substance familiarity. Participants ( n  = 470) completed a survey assessing familiarity and use of different substances, as well as perceptions regarding effects on the memory and credibility of intoxicated victims and witnesses. While participants most frequently reported believing that alcohol, hallucinogens, and polysubstance use of alcohol and cannabis have large negative effects on memory, they more frequently reported that they do not know the extent to which cannabis and cocaine affect memory. In addition, attitudes were found to vary based on substance familiarity. Differences with respect to the perceived impact on memory and credibility of various substances can have relevance to court proceedings, particularly in terms of voir dire procedures, jury instructions, and whether an expert witness is required to educate the court on the impacts of different forms of intoxication.